Reflective journaling: fostering dispositional development in preservice teachers. Issue 2 (3rd March 2016) - LaBelle, Jeffrey T.; Belknap, Gabrielle
Abstract: This study investigated the self-identified dispositions of 183 preservice teachers enrolled in a required philosophy of education course. The researchers coded their reflective journaling for the two essential NCATE (National Council for Accreditation of Teacher Education) dispositions of fairness and the belief that all students can learn, as well as for other recurring, self-identified dispositions. These preservice teachers self-identified fairness much more frequently than the belief that all students can learn. The results point to additional recurring dispositional themes for consideration: critical thinking, caring, openness, moral education, and individual freedom. Further examination of the data revealed great variation in the preservice teachers' interpretation of fairness, categorized as fairness through (1) inclusion of all socioeconomic classes and abilities; (2) culturally responsive teaching; (3) differentiation of instruction; and (4) fostering a safe learning environment.